The Effect of Social Media Promotion Mix and Destination Image on Visitor Satisfaction at Puncak Lima Jari, South Sulawesi - Nurul Muslihati Idris; I Made Sendra; Putu Sucita Yanthy (Cita Konsultindo Research Center, 2024)
In increasing visitor numbers, it is important to know and understand the factors that affect visitor satisfaction. In the context of the increasingly complex and competitive tourism sector, an effective promotion mix through social media and a positive destination image can be the key factors of increasing visitor satisfaction. This study aims to analyze the impact of social media promotion mix on visitor satisfaction at Puncak Lima Jari and analyze the influence of destination image on visitor satisfaction at Puncak Lima Jari. The research method uses a quantitative approach with data collection through the distribution of questionnaires to visitors who have visited Puncak Lima Jari. The sample for this study consists of 100 respondents, selected using purposive sampling techniques. Data analysis in this study is conducted using Structural Equation Modeling (SEM) with the SmartPLS4 analysis tool. The results of this study show that the social media promotion mix has a positive and significant effect on visitor satisfaction at Puncak Lima Jari, and the destination image also has a positive and significant effect on visitor satisfaction. This indicates that promoting Puncak Lima Jari and creating a positive destination image could increase visitor satisfaction. The implication of this study is to enhance the social media promotion mix and improve the positive image, which can provide greater satisfaction for visitors. Managers need to implement these strategies to attract more visitors in the future.